Clostridium difficile-derived membrane vesicles induce the expression of pro-inflammatory cytokine genes and cytotoxicity in colonic epithelial cells in vitro. (June 2017) - Nicholas, Asiimwe; Jeon, Hyejin; Selasi, Gati Noble; Na, Seok Hyeon; Kwon, Hyo Il; Kim, Yoo Jeong; Choi, Chi Won; Kim, Seung Il; Lee, Je Chul
Abstract: Clostridium difficile is the most common etiological agent of antibiotic-associated diarrhea in hospitalized and non-hospitalized patients. This study investigated the secretion of membrane vesicles (MVs) from C. difficile and determined the expression of pro-inflammatory cytokine genes and cytotoxicity of C. difficile MVs in epithelial cells in vitro . C. difficile ATCC 43255 and two clinical isolates secreted spherical MVs during in vitro culture. Proteomic analysis revealed that MVs of C. difficile ATCC 43255 contained a total of 262 proteins. Translation-associated proteins were the most commonly identified in C. difficile MVs, whereas TcdA and TcdB toxins were not detected. C. difficile ATCC 43255-derived MVs stimulated the expression of pro-inflammatory cytokine genes, including interleukin (IL)-1β, IL-6, IL-8, and monocyte chemoattractant protein-1 in human colorectal epithelial Caco-2 cells. Moreover, these extracellular vesicles induced cytotoxicity in Caco-2 cells. In conclusion, C. difficile MVs are important nanocomplexes that elicit a pro-inflammatory response and induce cytotoxicity in colonic epithelial cells, which may contribute, along with toxins, to intestinal mucosal injury during C. difficile infection. Highlights: C. difficile strains secrete spherical membrane vesicles (MVs) during in vitro culture. MVs of C. difficile ATCC 43255 contain a total of 262 proteins. C. difficile MVs stimulate the expression of pro-inflammatory cytokine genes in Caco-2 cells. C. difficile MVs induce cytotoxicity in Caco-2 cells. C. difficile MVs are important nanocomplexes that may contribute to bacterial pathogenesis.